A Bacterial Endophyte Bacillus amyloliquefaciens W10 Enhances the Tomato Resistance Against Tuta absoluta - Mingshi Qian; Chaoqi Sheng; Mingying Zheng; Ke Zhu; Youxin Yu; Gang Xu; Guoqing Yang (Agronomy)
The tomato leafminer, Tuta absoluta, is a destructive invasive tomato pest worldwide. Bacillus amyloliquefaciens W10, a bacterium isolated from the rhizosphere of tomatoes, is classified as a plant growth-promoting rhizobacterium. However, whether B. amyloliquefaciens W10 can improve the resistance of tomato against T. absoluta remains unclear. In this study, we found that B. amyloliquefaciens W10 promoted the tomato growth and significantly reduced the fecundity of T. absoluta. To further evaluate the effects of B. amyloliquefaciens W10 on the tomato’s resistance to T. absoluta, the age-stage, two-sex life table, and oviposition preference test were carried out to investigate the individual fitness, population parameters, and preference behavior of T. absoluta. Compared to the control, the intrinsic rate of increase (rm), net reproductive rate (R0), and finite rate of increase (λ) of T. absoluta in the treatment group were significantly reduced, while the population doubling time (DT) was significantly increased. Meanwhile, the oviposition preferences of T. absoluta for the treated tomato plants were reduced. After T. absoluta infestation, electrical conductivity and hydrogen peroxide (H2O2) content in tomato leaves after B. amyloliquefaciens W10 treatment were significantly lower than those in the control, while peroxidase (POD), polyphenol oxidase (PPO), jasmonic acid (JA), and salicylic acid (SA) levels were significantly higher. In addition, the O2−, superoxide dismutase (SOD), and catalase (CAT) levels were also affected. qRT-RCR analyses revealed that B. amyloliquefaciens W10 colonization induced the expressions of JA- and SA-related genes, including AOS1, AOC, PAL1, and SAMT, in tomato plants after T. absoluta infestation. These findings provide valuable insights and theoretical support for the application of beneficial endophytes to induce the resistance in tomatoes against T. absoluta.